Comparative Study of the Muscle Layers of The Rabbit Duodenum - Cheung, Waitak Donald (My University, 1979)
The studies presented in this thesis are the first attempts to compare in a comprehensive manner the basic electrical and mechanical properties of the two muscle layers of the small intestine of the rabbit, a species that showed electrical control activity (ECA). The activities of the two muscle layers were distinctly different. Cells in the longitudinal muscle layer (LM) were spontaneously active with action potentials occurring on every control potential (CP). Similarly, muscle strips dissected along the long axis of LM (LS) contracted spontaneously at the same frequencies as the ECA. Cells of the circular muscle layer (CM) usually did not exhibit spontaneous spiking activity although ECA was also present.
The characteristics of the ECA of the two muscle layers from the same muscle strips were similar in terms of amplitude, frequency, and their response to temperature change and external electrical stimuli. How the ECAs of the two muscle layers interact was investigated in light of the hypothesis that LM is the site of origin of ECA and that the ECA in CM is the result of electrotonic spread from LM (Bortoff, 1961, 1976; Connor, Kreulen, Prosser & Weigel, 1977). This hypothesis was tested directly in this study by measuring electrotonic coupling between the two muscle layers. It was found the there was little electrotonic interaction between muscle layers. Therefore, the result of this study is not consistent with the existing model in regard to the origin of the ECA.
Study of the control of muscle function by the intrinsic nerves also showed drastic differences between the two muscle layers. LM was innervate by cholinergic excitatory nerves and possibly by an inhibitory neural system. In CM, three types of neural excitatory events were identified in addition to the powerful non-adrenergic inhibitory nerves. Besides the familiar cholinergic excitatory nerves, a tetrodotoxin-resistant component and an excitatory response that emerged only after prolonged repetitive stimulation was also observed. The neurotransmitters for these two excitatory neural systems remain to be identified.
The results of this study indicate that the properties of the two muscle layers of the small intestine are very different. Nonetheless, normal physiological function of the intestine requires good coordination of the two muscle layers. The exact role of the individual layers in motility is not well defined. How these two muscle layers each with its separate neural, hormonal and local control mechanisms interact to produce the final intestinal motility pattern will be a challenging problem in the future.
Keywords: Medical Sciences; Medical Sciences